Analisis Kesalahan Berbahasa Indonesia dalam Kegiatan Presentasi Mahasiswa UIN SYAHADA Padangsidimpuan - Aisyah Siregar, Ummi; Aniati, Ira (Jurnal Hata Poda, 2022)
Language errors are often found in the activity of presenting papers in learning. The method used in this research is descriptive qualitative. The data in the research are in the form of words. This study aims to describe errors in Indonesian in the form of spelling in the activity of presenting papers in learning. The technique used for data collection in this study was observing and noting. Data analysis by classifying and grouping. The results of this study were errors in the language of presenting papers in learning including language errors in the form of variations in Indonesian including: Indonesian mixed with English; Indonesian mixed with the South Tapanuli Batak language. Keywords: analysis, language errors, learning Indonesian